Analysis of The Increase In National Health Insurance Contributions on The Rights and Obligations of Participants at the Puput Community Health Center (Puskesmas Puput) - Khoiriyah, Salsabila; Hidayat, Muhammad Syamsu (International Journal of Healthcare Research, 2024)
Background:  A total of 727 visits of JKN participants were served at Puput Bangka Barat Health Center. Based on the number of visits per month in January 2015, there were 1,536 cases served at eight Bangka Barat Health Centers. Based on the agreement, JKN participants in Bangka Barat Regency were budgeted by the Central Government, Bangka Belitung Provincial Government and Askes. The Bangka Barat community of JKN participants funded by the central government were 26,045 people, funded by the provincial government were 11,500 people and PNS, TNI, Polri were 13,865 people or a total of 51,419 people. Methods: This study used phenomenological research with a qualitative descriptive approach. The subjects of the study were key informants and triangulation informants totaling 10 informants at Puput Health Center. And the research instrument used in-depth interviews and documentation. Results:  participants did not feel the difference in health services, some of them felt for health services For routine contribution payments, informants pay contributions routinely according to their respective classes. Some complained about the increase in JKN contributions and some of them had no complaints about the increase in contributions. And for the perception of the increase in contributions, participants responded negatively to the government's policy related to the increase in BPJS Health contributions, although on the other hand they still hoped that the JKN contributions could be reduced. Conclusion: Utilization of Health Services at Puput Health Center, some of the participants were quite satisfied with the health services at Puput Health Center. Level of Compliance of JKN Participants in Making Routine Payments of JKN Contributions, there were participants who did not pay contributions on the grounds that they were due to the increase in contributions. And the perception of participants about the policy of increasing JKN contributions in JKN membership, policies related to BPJS Health, informants strongly objected to this policy.